2019
DOI: 10.1111/jfpp.13915
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pretreatment and spray drying on the physicochemical properties and probiotics viability of Moringa (Moringa oleiferaLam) leaf juice powder

Abstract: Spray drying was investigated in this study to produce Moringa leaf powder which was examined for its nutritional value and ability to support probiotics during storage with and without pretreatment. Response surface methodology with central composite rotatable design was performed to optimize the drying process for maximum yield based on two independent variables: inlet air temperature (116–144°C) and feed maltodextrin concentration (8.0%–22.5% w/w). The responding factors include drying characteristics (yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…For example, De Liz et al (2020) found variations between 0.32-0.33 and 0.54-0.55 g cm −3 , respectively, for loose and tapped bulk densities of spray-dried powders with goat's whey freeze concentrate and inulin, and with only goat's whey freeze concentrate, respectively. Looi et al (2019) found 0.36-0.45 and 0.52-0.64 g cm −3 , respectively, for loose and tapped bulk densities for probiotic spray-dried powders from Moringa oleifera Lam. The change in specific volume between the loose and tapped bulks is recognised as interstitial air content (IA; Wu et al, 2019).…”
Section: Spray-dried Powder Propertiesmentioning
confidence: 97%
“…For example, De Liz et al (2020) found variations between 0.32-0.33 and 0.54-0.55 g cm −3 , respectively, for loose and tapped bulk densities of spray-dried powders with goat's whey freeze concentrate and inulin, and with only goat's whey freeze concentrate, respectively. Looi et al (2019) found 0.36-0.45 and 0.52-0.64 g cm −3 , respectively, for loose and tapped bulk densities for probiotic spray-dried powders from Moringa oleifera Lam. The change in specific volume between the loose and tapped bulks is recognised as interstitial air content (IA; Wu et al, 2019).…”
Section: Spray-dried Powder Propertiesmentioning
confidence: 97%
“…Nonetheless, aspect ratio and moisture content imperatively affected the frictional and mechanical properties of moringa. So far, research studies have reported only on changes in quality, nutritional and textural attributes of moringa leaf powder using different drying techniques and various drying temperatures (Premi et al, 2012; Saini et al, 2014; Verma et al, 2015; Looi et al, 2019; Manju et al, 2021), frictional properties of moringa pods (Sudagar et al, 2021), and moisture‐dependent physical properties of moringa seeds (Aviara et al, 2013). There were no investigations on the frictional and mechanical characteristics of moringa pods concerning to aspect ratio and moisture content.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, from Table 2, a yield of 57.77% obtained by using the spray-drying conditions of this study, is one of the highest values achieved for plant and fruits extractions (da Silva et al, 2019;Looi et al, 2019). About a moisture content of 6.65%, measured on microencapsulated M. zapota pulp, is attributable to hydrophilic groups from MD (Niamnuy et al, 2019).…”
Section: Physicochemical and Antioxidantmentioning
confidence: 55%